Plataforma virtual para potenciar la gramática y vocabulario en inglés en primaria - Yalta Chuquimbalqui, Jose Luis (2024)
The present proposal for educational innovation addresses the need to enhance English grammar and vocabulary skills among elementary students, emphasizing the importance of addressing these aspects from an early age. Thus, the development of an interactive virtual platform is proposed as an innovative solution tailored to educational needs within a public school in Lima. The methodology involved a literature review encompassing two general aspects in primary education: LMS virtual platforms and grammar/vocabulary in English language teaching. The evaluation methodology applied was quantitative to measure student achievement levels before and after platform implementation, and qualitative to analyze the project's impact on various stakeholders within the educational institution, achieved through surveys, grade comparisons, and checklists. The overall objective focuses on analyzing the effectiveness of integrating the interactive virtual platform to improve English grammar and vocabulary levels. Results indicate the platform's contribution to enhancing English grammar and vocabulary skills. The analysis underscores students' preference for digital learning and the use of virtual platforms. Conclusions provide a robust foundation for the successful development and implementation of this educational tool.